2019
DOI: 10.1097/ncq.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Atrial Fibrillation Care After an Emergency Department Visit

Abstract: Background: Between 2010 and 2012, the Heart Rhythm team in a tertiary care hospital completed a retrospective study that found that atrial fibrillation (AF) care can be episodic and heavily reliant on hospital resources, particularly the emergency department (ED). Problem: Patients who attend the ED with AF are at high risk of hospital admission. Approach: A nurse practitioner (NP) was added to the Heart Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…None presented randomized controlled trials. These articles were, respectively, a retrospective, descriptive, exploratory report (Hart et al, 2019); a qualitative descriptive study (Rush, Hatt, et al, 2019); and a mixed-methods study (Rush, Burton, et al, 2019). This finding confirms a lack of literature concerning AF telehealth education and treatment programs unrelated to postablation or early detection of atrial fibrillation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…None presented randomized controlled trials. These articles were, respectively, a retrospective, descriptive, exploratory report (Hart et al, 2019); a qualitative descriptive study (Rush, Hatt, et al, 2019); and a mixed-methods study (Rush, Burton, et al, 2019). This finding confirms a lack of literature concerning AF telehealth education and treatment programs unrelated to postablation or early detection of atrial fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…Without specialized care, patients may not receive needed oral anticoagulation. One study indicated that 15% of all strokes in the general population are linked to AF (Hart et al, 2019). Additionally, inadequately managed AF leads to a fivefold increase in reported psychosocial distress and worsening quality of life (Rush, Burton, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result is fragmentation of care, leading to repeated emergency department evaluations and escalated healthcare costs. 1 Allied health professionals (AHPs) in cardiac electrophysiology have the expertise to deliver integrated AF care through telemedicine. Such a program has the potential to expand access to specialized AF care and improve outcomes.…”
Section: Introductionmentioning
confidence: 99%